Solid-state fermentation of hemp waste: enhancing the performance of Hermetia illucens larvae and altering the composition of hemp secondary metabolites - Yakti, Wael; Förster, Nadja; Müller, Marcus; Beck, Sebastian; Schulz, Simon; Mewis, Inga; Ulrichs, Christian (Frontiers in Bioengineering and Biotechnology, 2025)
Solid-state fermentation (SSF) can increase the nutritional quality of low value substrates for insects. In this study, SSF using different fungal species was applied on a hemp waste substrate, and the fermentation was followed by a black soldier fly larvae (BSFL) feeding experiment during which 300 larvae were grown on 200 g (20.1% DM) substrate for 7–9 days depending on the treatment. Besides assessing the BSFL performance parameters, the presence of hemp cannabinoids, flavonoids, and terpenes was assessed through the process and compared among the treatments. The results show that BSFL growth parameters varied depending on the fungal species used. Fermenting the substrate with Ganoderma lucidum can lead to an increase in the BSFL dry yield (4.54 g) compared to the untreated substrate (2.86 g), likely due to enhancing carbon accessibility in the substrate. SSF using Trichoderma reesei increased the cannabidiol and ∆9-tetrahydrocannabinol mass fractions in the substrate, and consequently in the produced BSFL biomass, while decreasing the amounts of acidic cannabinoids. Both Hypsizygus ulmarius and Pleurotus ostreatus effectively removed cannabinoids from the substrate. This study confirms that pre-treating hemp wastes via SSF can enhance their nutritional value and/or reduce bioactive secondary metabolites, with different fungal species offering different and complementary performances in achieving different biotechnological goals.